Clinic management system :drug information management system - Nur Syuhada, Mohamad Rodzi (2005)
Drug Information Management System is a system that provides electronic drug references data in the pharmacology field. The doctors and pharmacists always refer to the drug references data in order to know the details about the specific drug data. At the government hospital, the process of finding the drug references data still done in manual way by drug references books. Other than that, the drug references books are outdated. There are no standard drug references systems that can be refer by the doctors and pharmacists. To solve these problems, a system to transform the manual process of finding drug references data into the computerized system is implemented. By transforming the manual drug references data into the management system, the doctors and pharmacists time for searching the drug data for references can be reduced. Beside, the drug references data can be updated as soon as possible if the immediate update is needed and doctors and pharmacists are able to view the updated data.